Pengaruh Faktor Sosial Demografi Terhadap Lama Mencari Kerja di Sumatera Barat - Rita Wati; Ariusni Ariusni (Universitas Negeri Padang, 2023)
This study aims to determine and analyze; (1) What is the effect of educationon the length of time looking for work in Sumatra? West, (2) What is theeffect of age on the length of time looking for work in West Sumatra, (3) theextent to which gender influences the length of time looking for work in WestSumatra, (4) the extent to which training affects the length of time lookingfor work in West Sumatra (5) the extent to which the effect of education, age,gender and training on the length of time looking for work in West Sumatra.This research is a descriptive and associative research that uses Sakernasdata in 2020 with 894 samples. The results showed that (1) Education had apositive and insignificant effect on the length of time looking for work inWest Sumatra, (2) Age had a positive and insignificant effect on the length oftime looking for work in West Sumatra, (3) age had a positive andsignificant effect on the length of time looking for work in West Sumatra.West Sumatra, (4) training has a negative and significant effect on the lengthof time looking for work in West Sumatra. So it can be concluded thateducation, age, training and gender are important aspects in finding a job inWest Sumatra.